2015
DOI: 10.1371/journal.pone.0119801
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Depletion by Arginine Deiminase Does Not Affect Whole Protein Metabolism or Muscle Fractional Protein Synthesis Rate in Mice

Abstract: Due to the absolute need for arginine that certain cancer cells have, arginine depletion is a therapy in clinical trials to treat several types of cancers. Arginine is an amino acids utilized not only as a precursor for other important molecules, but also for protein synthesis. Because arginine depletion can potentially exacerbate the progressive loss of body weight, and especially lean body mass, in cancer patients we determined the effect of arginine depletion by pegylated arginine deiminase (ADI-PEG 20) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…observed tissue-specific protein FSR values were comparable to those reported using D 2 O [7,20,32] and [ 2 H 5 ]phenylalanine flood dose methods [33,34] in mice [33], rat [7], and humans [20].…”
Section: Plos Onesupporting
confidence: 82%
“…observed tissue-specific protein FSR values were comparable to those reported using D 2 O [7,20,32] and [ 2 H 5 ]phenylalanine flood dose methods [33,34] in mice [33], rat [7], and humans [20].…”
Section: Plos Onesupporting
confidence: 82%
“…In this study, ADI-PEG20 resulted in the depletion of circulating arginine as previously reported (9,17). As a consequence, plasma citrulline concentrations and fluxes were greater in these mice.…”
Section: Discussionsupporting
confidence: 81%
“…The administration of ADI-PEG20 disrupts the interorgan metabolism of arginine, because all circulating arginine is converted into citrulline and any arginine synthesized and exported by the kidney is then converted back to citrulline upon entering the circulation. Although circulating arginine is considered essential for blood pressure maintenance (33), the depletion of arginine per se has little consequence on the metabolism of animals and humans when citrulline is available for local arginine synthesis (9,16,17). This is best exemplified by arginine depletion by arginase, which results in weight loss and death, but that can be prevented by citrulline supplementation (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The citrulline produced by the enterocytes enters the portal circulation, bypasses the liver, enters the general circulation and is utilized by the kidney and other tissues for the synthesis of arginine [20▪,21▪]. Small amounts of circulating citrulline are produced as co-product in the synthesis of nitric oxide and in the turnover of posttranslational modified arginine (citrullinated and methylated).…”
Section: Introductionmentioning
confidence: 99%